2022
DOI: 10.14814/phy2.15208
|View full text |Cite
|
Sign up to set email alerts
|

The effects of whole‐body vibration amplitude on glucose metabolism, inflammation, and skeletal muscle oxygenation

Abstract: Whole‐body vibration (WBV) is an exercise mimetic that elicits beneficial metabolic effects. This study aims to investigate the effects of WBV amplitude on metabolic, inflammatory, and muscle oxygenation responses. Forty women and men were assigned to a high (HI; n = 20, Age: 31 ± 6 y) or a low‐amplitude group (LO; n = 20, Age: 33 ± 6 y). Participants engaged in 10 cycles of WBV [1 cycle =1 min of vibration followed by 30 s of rest], while gastrocnemius muscle oxygen consumption (mVO2) was assessed using near‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…It was also found that after 30 minutes of rest after WBV, there was a reduction of 21.8% in the acute phase and we noticed an increase in glycemia of 3.1% in the chronic phase. This result was similar to that found by Sanni et al [21], as the low-amplitude EWBV contributed to a more favorable improvement in glucose metabolism when compared to high-amplitude WBV.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It was also found that after 30 minutes of rest after WBV, there was a reduction of 21.8% in the acute phase and we noticed an increase in glycemia of 3.1% in the chronic phase. This result was similar to that found by Sanni et al [21], as the low-amplitude EWBV contributed to a more favorable improvement in glucose metabolism when compared to high-amplitude WBV.…”
Section: Discussionsupporting
confidence: 91%
“…The studied individual has risk factors for cardiovascular diseases, obesity, and a sedentary lifestyle. Physical inactivity increases the relative risk of developing type 2 diabetes mellitus by up to 112% [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise (Petersen and Pedersen, 2005 ) and WBV (Jawed et al, 2020 ; Sanni et al, 2022 ) are associated with anti-inflammatory effects. This anti-inflammatory property may extend to neuroinflammation (Mee-Inta et al, 2019 ; Chen et al, 2022 ; Oroszi et al, 2022a ).…”
Section: Discussionmentioning
confidence: 99%
“…Sanni et al investigated the acute effects of WBV (HI = 88.7 ms 2 and LO =44.4 ms 2 , both at 30 Hz) in healthy volunteers. They report a higher muscle oxygen consumption in the LO compared to the HI group and an increase in IL-6 in both groups but a higher in the LO [ 165 ]. Rodriguez-Miguelez studied healthy elderly volunteers (70 years) who performed an 8-week training protocol on WBV.…”
Section: Whole-body Vibrationmentioning
confidence: 99%